Literatur Review: Analisis Job Description Terhadap Kepuasan Kerja - Lutfiyani, Mawarda; Manik, Samantha Petricia; Maulitya, Tannya Athalla; Novitrisani, Yulinda; Merdianty, Netty (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Human Resources (HR) is a very important aspect that plays a role in a company to ensure organizational processes run effectively. Employees need to understand the ins and outs of their work in order to be able to carry out their work optimally and fulfill the needs and responsibilities of their position. Job description is a clear and detailed description or guideline that must be completed by an employee. The literature review method was carried out by collecting books and journals from various information sources, both national and international. It was found that there were significant results between the influence of job descriptions on job satisfaction. Employees who have clarity regarding their duties will be more focused in understanding the direction of their work, and in the end can achieve maximum performance results and bring job satisfaction.